The Association Between Social Media Addiction and Mental Health Among Generation Z: A Cross-sectional Study in University X-West Sumatera, Indonesia - Elsi Novnariza; Yudi Pradipta; Saidati Ashfi Dzakiya Henda; Aisyah Jannatus Shabrina (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Mental health issues among adolescents in Indonesia are significant public health concern, with the prevalence rate reported 9.8%. Advances in information technology and widespread use of social media are factors that bring benefits as well as adverse effects on adolescent mental health. The study aimed to examine the association between social media addiction and the mental health of Generation Z college students. We used a cross-sectional study on May-July 2024 in University X, West Sumatera Province. The sample was 140 students based on Lemeshow's sample size formula. We conducted purposive sampling in 15 faculties proportionally. Data were collected through interviews using structured questionnaires adopted from Social Media Addiction Scale (SMAS) and Self Report Questionnaire (SRQ)-20. Data were analyzed using linear regression test with 95% Confidence Interval. The Majority of respondents were female (60%), from 2023 cohort (26.43%), and lived in a boarding house (76.43%). The most frequently used social media by respondents were: Instagram (68.6%), TikTok (55%), and WhatsApp (50%). The most significant relationship (p-value<0.001) was found between social media addiction and students' mental health adjusted by gender, residential, and admission year of students. These findings suggest that social media addiction related to mental health issues among college students. It is recommended that the university collaborate with the health service to conduct regular screening and mental health assesment for students. Keywords: College Students, Generation Z, Mental Health, Social Media Addiction